Assessing the economic implications of land returned to the Te Hiku iwi collective, Tai Tokerau, Aotearoa New Zealand. (May 2021) - McDonald, G.W.; Kingi, T.T.; Kim, J.-H.; Dowling, L.; Journeaux, P.; Dunningham, A.; Wakelin, S.; Monge, J.; Hock, B.
Highlights: Considers returned rural land associated with historical grievances. Considers economic, socio-cultural and environmental objectives in land development. Develops a multi-regional and fully dynamic computable general equilibrium model. Couples geospatial, partial and computable general equilibrium models. Multi-scale integrated assessment with uncertainty quantified.